Advancing feminist understandings of woman abuse: the value of old wine in new bottles - Walter S. DeKeesredy (Frontiers in Sociology)
Despite making some of the most important advances in the social scientific study of woman abuse, feminist sociological research and theorizing that prioritize the concept of patriarchy have leveled off or declined in the last 15 years due, in large part, to the current hegemony of mainstream criminologists fundamentally opposed to a rich gendered understanding of one of the world's most compelling social problems. Drawing on nearly 50 years of research done by an international cadre of highly experienced scholars, this article demonstrates the importance of revisiting some major feminist conceptual, empirical, and theoretical contributions from the past. Recommended here are gender-specific conceptualizations of abuse, in-depth reviews of the extant literature, self-report surveys of potential male offenders, quantitative indicators of men's patriarchal attitudes and beliefs, and supplementary open-ended survey questions.